Effect of Oxytocin Massage on Breast Milk Production among Postpartum Mothers - Nike Andika Sari; Sunanto; Tutik Hidayati (KHD Production, 2023)
Exclusive breastfeeding in the world is still very low. Various obstacles can arise in providing exclusive breastfeeding during the first six months of a baby's life. This causes a lack of provision of nutrients to infants, which can cause infant death. In a preliminary study conducted in the Postpartum Room at Bhayangkara Lumajang Hospital in February 2022, based on the results of interviews with 10 normal postpartum mothers, it was found that postpartum mothers complained that their milk did not come out and was not smooth and felt that their milk production was lacking, especially on the first day of the baby's birth. This study aimed to analyze the effect of oxytocin massage on breast milk production in postpartum mothers at Bhayangkara Lumajang Hospital. This type of research is pre-experiment by designing one group pre-post test design. Sampling using the method of simple random sampling with a sample of 36 respondents was carried out in August 2022. The instrument used for data collection was a checklist sheet. The results showed that almost all 36 respondents to produce milk after having oxytocin massage for postpartum mothers at Bhayangkara Lumajang Hospital in 2022 were in the current category with a total of 33 respondents (91.7%). It obtained a p-value=0.000, which means that oxytocin massage affects breast milk production (ASI) in postpartum mothers at Bhayangkara Lumajang Hospital.